FRI0229 Henoch-schoenlein purpura nephritis and IGA nephropaty: A comparative clinical study. (23rd January 2014) - Rueda-Gotor, J.; Calvo-Río, V.; Martín, L.; Loricera, J.; Ortiz-Sanjuán, F.; Lamuño, D.; González-Lόpez, M.A.; Fernández-Llaca, H.; González-Vela, M.C.; Arias, M.; Peirό, E.; González-Gay, M.A.; et al.
Abstract : Background: Henoch-Schonlein Purpura Nephritis (HSPN) and IgA Nephropathy (IgAN) have been traditionally considered related diseases Objectives: To establish the possible differences and similarities between both entities. Methods: Study of an unselected population of 141 patients with HSPN and 55 with IgAN from a teaching hospital. HSP was diagnosed according to the criteria proposed by Michel et al (J Rheumatol 1992). IgAN was diagnosed according to renal biopsy in 49 patients, in the remaining 6 cases biopsy was not performed due to typical clinical features. The statistical analysis was performed with the STATISTICA software (Statsoft Inc.). Continuous variables (normally and not normally distributed) were compared with the 2-tailed Student's t-test or the Mann-Whitney U test, respectively. The chi-square test was used for the dichotomous variables. Results: The mean age at onset was of 28.7±26.6 years (range; 2-84) in HSPN and 35.5±13.2 (range; 12-68) in IgAN (p=NS). Most patients in both conditions were male; 56.7% in HSPN and 63.6% in IgAN (p=NS). Precipitating events were found in 58 (41.2%) of patients with HSPN and 5 (27.3%) cases with IgAN (p= NS). The most frequent precipitating events in HSPN and IgAN were respectively drug intake (22% vs 22.5%; p NS) and an upper respiratory tract infection (34.5% vs 19.5%; p=NS). Extra-renal manifestations were more common in HSPN [skin (97.1% vs 18.6%; p<0.001), gastrointestinal (68.8% vs 14.6%; p<0.001), and joint involvement (64.5% vs 7%; p<0.001)]. Renal involvement was more severe in IgAN [renal insufficiency (15.5% vs 54.5%; p<0.001); nephrotic syndrome (11% vs 52.8%; p<0.001), and nephritic syndrome (11% vs 18.2%; pNS)]. Anemia was more common in IgAN (11.4% vs 31.2%, p=0.001). Increased serum levels of IgA were similar (58% in HSPN vs 71.4% in IgAN; p= NS). C4 was decreased in 10.7% (10 of 93 tested) patients with PSHN and in 0 of 39 patients with IgAN (p=0.03). Renal biopsies were performed in 16 patients with PSHN and in 49 with IgAN. The main histological findings were similar in both groups, in most cases mesangial hypercellularity with deposits of IgA and C3 in the mesangium. Drug therapy requirement was similar (57.1% in HSPN vs 69.2% in IgAN; p=NS). However, the initial corticosteroid dose was higher in IgAN (mean prednisone in mg/day; 35.5±15.5 vs 57.5±14.7, p=0.002). The disease relapsed in 36.4% of PSHN and in 58.8% of the IgAN (p=NS). After a median follow-up of 48 months; interquartile range (5.5, 60) and 48 months (12, 139), persisting mild renal insufficiency was observed in 4 and 6 cases and mild hematuria in 26 and 2 cases with PSHN and IgAN, respectively. Conclusions: Our study shows that IgAN patients exhibit more severe renal involvement, with a higher frequency of renal insufficiency and nephrotic syndrome. As expected, extra-renal involvement was more frequent in HSPN. However, the final outcome was equally good in most patients with both diseases. Disclosure of Interest: None Declared